Deletion of hypoxia-responsive microRNA-210 results in a sex-specific decrease in nephron number - Hemker, Shelby L (FASEB J, 2020)
Low nephron number results in an increased risk for developing hypertension and chronic kidney disease. Intrauterine growth restriction is associated with a nephron deficit in humans, and is commonly caused by placental insufficiency, which results in fetal hypoxia. The underlying mechanisms by which hypoxia impacts kidney development are poorly understood. microRNA-210 is the most consistently induced microRNA in hypoxia and is known to promote cell survival in a hypoxic environment. In this study, the role of microRNA-210 in kidney development was evaluated using a global microRNA-210 knockout mouse. A male-specific 35% nephron deficit in microRNA-210 knockout mice was observed. Wnt/β-catenin signaling, a pathway crucial for nephron differentiation, was mis-regulated in male kidneys with increased expression of the canonical Wnt target lymphoid enhancer binding factor 1. This coincided with increased expression of caspase-8-associated protein 2, a known microRNA-210 target and apoptosis signal transducer. Together, these data are consistent with a sex-specific requirement for microRNA-210 in kidney development.